Investigasi Pemecahan Masalah Matematika Berdasarkan Kategori Adversity Quotient pada Siswa Kelas XII - Rosikhoh, Dewi; Firdiansyah, Adin Lazuardy; Hasanah, Riskiyatul (Jambura Journal of Mathematics Education, 2023)
In this manuscript, our research purpose was to describe how high school students solved geometry problems in terms of Adversity Quotient (AQ). This research was qualitative descriptive research. The subjects of this research were five students in grade 12 science divided into one climber student, one camper-climber student, two camper students, and one quitter-camper student. In this research, we used some instruments, namely the ARP questionnaire, problem-solving test questions, and interview guidelines. The qualitative data were analyzed by using the principles or steps of the Polya method in solving problems. The results showed that the climber and camper-climber students could understand the problem, make plans, carry out plans, and check back in solving the geometry problems. However, the camper-climber student in re-checking answers had not been equipped with other strategies or methods. The camper student could understand the problem, make plans, and carry out plans in solving the problems. It was just that the camper student making plans was not more complex than the plans made by the climber student. Meanwhile, the quitter-camper student could only understand the problem. Therefore, AQ categories of students could be used as one of the teacher considerations in forming groups when learning mathematics in class, especially in trying students' problem-solving skills.